Reconstructing liquefied natural gas charter party clauses to address emis-sion obligations under international shipping decarbonisation - Alqadri Wijaya Putra; Mickray Goldsteina Sombowadile; Muhammad Haikal Kafi (Institute for Law and Economics Studies, 2026)
The global energy transition has accelerated the adoption of Liquefied Natural Gas (LNG) as a transitional marine fuel, yet its expanding use in shipping increasingly conflicts with stricter decarbonisation requirements under the International Maritime Organization (IMO) regime, creating tension within existing contractual frameworks. This study employs a normative (doctrinal) legal research methodology, integrating statutory, conceptual, and comparative approaches to examine MARPOL Annex VI amendments, standard LNG charter party forms issued by BIMCO and GIIGNL, and relevant maritime law and engineering literature. The analysis evaluates the alignment of these instruments with the Energy Efficiency Existing Ship Index (EEXI) and Carbon Intensity Indicator (CII), both mandatory since January 2023. Findings reveal four key contractual gaps: lack of clear CII responsibility allocation, conflict between speed warranties and emission-driven reductions, absence of methane emission regulation for boil-off gas and engine slip, and resulting legal uncertainty and compliance risks. To address these issues, the study proposes four model clauses Emission Responsibility, CII Compliance, Speed-Emission Adjustment, and LNG Methane Emission based on control-based liability and causation-based cost allocation, positioning LNG charter parties as instruments of both commercial governance and environmental compliance.